Validated simultaneous spectrophotometric quantification of a new antiviral combination - Abdel-Gawad, Sherif Abdel-Naby (European Journal of Chemistry, 2017)
Simple, selective and precise spectrophotometric methods were applied for simultaneous quantification of sofosbuvir (SFV) and ledipasvir (LDI) both in their raw and dosage forms. In the first method, the two cited drugs were determined simultaneously using first derivative (D1) method. It was accomplished by measuring peak heights at 275 nm and 344 nm, for SFV and LDI, respectively, in concentration ranges of 5 - 80 μg/mL and 3 - 50 μg/mL, for SFV and LDI, respectively. In the second one, a first derivative of ratio spectra (1DD) method was adopted to quantify SFV in concentration range of 5 - 80 µg/mL. It was adopted by measuring the peak amplitudes (valley and peak) at 259 nm and 280 nm, using 25 µg/mL LDI as a divisor. The proposed method was also used to determine LDI in concentration range of 3 - 50 µg/mL by recording the peak amplitudes (valley and peak) at 319 nm and 375 nm, using 80 µg/mL SFV as a divisor. The developed methods were validated with respect to linearity, accuracy, precision, selectivity, robustness and limits of detection and quantification (LOD and LOQ), as per the guidelines of International Conference on Harmonization (ICH)-Q2B.